Advances in Food and Non-Food Biomass Production, Processing and Use in Sub-Saharan Africa: Towards a Basis for a Regional Bioeconomy - Schmitt, Christine B. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The bioeconomy concept aims to add sustainability to the production, transformation, and trade of biological goods. Though implemented around the world, the development of national bioeconomies is uneven, especially in the global South, where major challenges exist in Sub-Saharan Africa. In this context, the international BiomassWeb project aimed to underpin the bioeconomy concept by applying the value web approach, which seeks to uncover complex interlinked value webs instead of linear value chains. The project also aimed to develop intervention options to strengthen and optimize the synergies and trade-offs among different value chains. The Special Issue "Advances in Food and Non-Food Biomass Production, Processing and Use in Sub-Saharan Africa: Toward a Basis for a Regional Bioeconomy"" compiles 23 articles produced in this framework. The articles are grouped in four sections: the value web approach; the production side; processing, transformation and trade; and global views.